Short and long‐term outcomes of chronic pulmonary hypertension in preterm infants managed using a standardized algorithm. Issue 5 (14th December 2020) - Baczynski, Michelle; Kelly, Edmond; McNamara, Patrick J.; Shah, Prakesh S.; Jain, Amish
Abstract: Background: There is limited data on management strategies for chronic pulmonary hypertension (cPH) in chronic lung disease (CLD) of prematurity. Our objective was to evaluate clinical outcomes following a standardized policy, wherein only cPH with right‐ventricular (RV) dilatation was treated and diuretics were employed as first‐line therapy; cPH without RV‐dilatation was managed expectantly. Method: In this retrospective cohort study, all infants with CLD were categorized as "CLD‐only" or "CLD–cPH, " using echocardiography at ≥36 weeks postmenstrual age. Intergroup comparison was performed. Regression analysis examined the association between cPH and primary outcome of death or disability at 18–24 months. Results: Of 128 CLD infants, 48 (38%) had cPH, of which 29 (60%) received diuretics. Symptomatic improvement within 1‐week was recorded in 90%. Although CLD–cPH had worse in‐hospital respiratory course than CLD‐only, all post‐discharge respiratory and neurodevelopmental outcomes were similar. cPH was not associated with death or disability (adjusted odds ratio, 1.02; 95% confidence interval, 0.32–3.27). Disease progression treated with sildenafil occurred in 2 (4%) cases. There was no death from respiratory or RV failure. Conclusion: Primary treatment of CLD–cPH with diuretics using RV‐dilatation as therapeutic threshold, may result in symptomatic improvement, disease stabilization and post‐discharge outcomes comparable to infants without cPH.